Ficolin-2 serum levels predict the occurrence of acute coronary syndrome in patients with severe carotid artery stenosis. (April 2021) - Carbone, Federico; Valente, Alessia; Perego, Carlo; Bertolotto, Maria; Pane, Bianca; Spinella, Giovanni; Palombo, Domenico; De Simoni, Maria-Grazia; Montecucco, Fabrizio; Fumagalli, Stefano
Graphical abstract: Abstract: Background and purpose: erosion of vulnerable atherosclerotic plaques may cause life-threatening thromboembolic complications. There is indeed an urgent need to recognize a clear-cut biomarker able to identify vulnerable plaques. Here, we focused on circulating proteins belonging to the lectin pathway (LP) of complement activation. Methods: we analyzed mannose-binding lectin (MBL), ficolin-1, -2 and -3 (LP initiators) levels by ELISA in sera from n = 240 of an already published cohort of patients undergoing endarterectomy for severe carotid stenosis and followed-up until 18 months after surgery. Immunofluorescence followed by confocal and polarized light microscopy was used to detect LP initiator intraplaque localization. Spearman's rank test was drawn to investigate correlation between serum LP levels and circulating inflammatory proteins or intraplaque components. Survival analyses were then performed to test the predictive role of LP on long-term adverse outcome. Results: ficolins, but not MBL, correlated positively with 1) high circulating levels of inflammatory markers, including MPO, MMP-8, MMP-9, ICAM-1, osteopontin, neutrophil elastase, and; 2) immune cell intraplaque recruitment. Immunofluorescence showed ficolins in calcified plaques and ficolin-2 in cholesterol-enriched plaque regions in association with macrophages. In the multivariate survival analysis, ficolin-2 serum levels predicted a major adverse cardiovascular event during the follow-up, independently of symptomatic status and inflammatory markers (hazard ratio 38.6 [95 % CI 3.9–385.2]). Conclusions: ficolins support intraplaque immune cell recruitment and inflammatory processes ultimately leading to plaque vulnerability. Especially for ficolin-2 a strong predictive value toward adverse cardiovascular events was demonstrated. This evidence offers potentially new pharmacological target to dampen the inflammatory mechanisms leading to plaque vulnerability.